Brain Twister Puzzle

Brain Twister Puzzle Solution - 28 july

2+3=8,
3+7=27,
4+5=32,
5+8=60,
6+7=72,
7+8=??

Solve it?

For Solution : Click Here

119 comments:

  1. Replies
    1. Your are the real genius.

      Delete
    2. It's "You're the real genius"

      Delete
    3. wow but try to solve 84*[2+2+2]!.

      Delete
    4. in other way it can be solved as a*(b+(a-1))

      Delete
    5. This comment has been removed by the author.

      Delete
    6. (a * b) + (a * (a-1))
      (7 * 8) + (7 * 6) = 98

      Delete
    7. its 98
      2*(3+1)=8
      3*(7+2)=27
      4*(5+3)=32
      5*(8+4)=60
      6*(7+5)=72
      7*(8+6)=98

      Delete
    8. 2*1+(2*3)=8
      3*2+(3*7)=21
      4*3+(4*5)=32
      5*4+(8*5)=60
      6*5+(7*6)=72
      7*6+(8*7)=98

      Delete
    9. (2*3)+2=8
      (3*7)+6=27 (:6-2=4)
      (4*5)+12=32 (:12-6=6)
      (5*8)+20=60 (:20-12=8)
      (6*7)+30=72 (:30-20=10)
      (7*8)+42=98 (:42-30=12)

      Delete
    10. Siddaram S I
      2*3=6(+2=0+2)
      3*7=21(+6=2+4)
      4*5=20(+12=6+6)
      5*8=40(+20=12+8)
      6*7=42(+30=20+10)
      7*8=56(+42=30+12)

      Delete
    11. ∑ c(n-1)+d(n) - (∑ c(n-1)+d(n) - ∑ a(n-1)+b(n)) = u
      n = 2 n = 3

      2(1) + 3(2) = 8 = u
      3(2) + 7(3) = 27
      4(3) + 5(4) = 32
      5(4) + 8(5) = 60
      6(5) + 7(6) = 72
      7(6) + 8(7) = 98

      Delete
    12. Steve Jobs

      Thought exactly like that, although without this part:

      "∑ c(n-1)+d(n) - (∑ c(n-1)+d(n) - ∑ a(n-1)+b(n)) = u
      n = 2 n = 3"

      ... I'm just inthe 9th grade (from Portugal).

      Delete
    13. Its 98

      Add both numbers
      then multiply the result with first number
      and then subtract the first number with the result

      therefore: 7+8 = 15
      then 15 X 7 = 105
      then 105 - 7 = 98

      Delete
    14. Answer is 98.. this is how we get:
      [2]+3=8............... 2*3+2 (2 is the initial product)
      [3]+7=27............. 3*7+6 (2*3)
      [4]+5=32............. 4*5+12 (4*3)
      [5]+8=60............. 5*8+20 (5*4)
      [6]+7=32............. 6*7+30 (6*5)
      [7]+8=32............. 7*8+42 (7*6)


      Rule: Multiply both numbers and add a [NUMBER]

      this Number is found by multiplying the first number of the row with the previews number respectively, shown in square brackets.

      Delete
  2. Replies
    1. yes < because 9de-shift0
      @89#=!0+*<
      #89&=@0+@&<
      $89%=#0+#@<
      %89*=$0+^)<
      ^89&=%0+&@<
      &89*=^0+(*>

      Delete
  3. A*b + a*(a-1)
    Or
    A*(a+b-1)
    Or
    A*a + a*b -a

    ReplyDelete
  4. 2*(3+1)=4
    3*(7+2)=27,
    4*(5+3)=32,
    5*(8+4)=60,
    6*(7+5)=72,
    7*(8+6)=98

    ReplyDelete
  5. Replies
    1. 2*(3+1)=4
      3*(7+2)=27,
      4*(5+3)=32,
      5*(8+4)=60,
      6*(7+5)=72,
      7*(8+6)=98

      Delete
  6. a+b=c
    c/a=d
    d=a+b-1
    7+8=15;15-1=14;14*7=98
    7+8=98

    ReplyDelete
  7. ans is 98...
    (2*3)+2 = 8
    (3*7)+6 = 27
    (4*5)+12 = 32
    5*8 + 20 = 60
    6*7 + 30 = 72
    7*8 + 42 = 98

    ReplyDelete
    Replies
    1. I still did not get it!
      :(

      Delete
  8. 2+3=5
    5*2=10
    10-2=8


    3+7=10
    10*3=30
    30-3=27


    similarly
    7+8=15
    15*7=105
    105-7=98

    ReplyDelete
  9. A+B=C
    D+E=F

    Rule: F = ((D+E)*A) + E

    Thus, ans is 98.

    -Manoranjan

    ReplyDelete
  10. Wrong the answer is 98 try to analyze the problem.... you will still get the correct answer.....

    ReplyDelete
  11. (2*3)+(2*1)=8
    (3*7)+(3*2)=27
    (4*5)+(4*3)=32
    (5*8)+(5*4)=60
    (6*7)+(6*5)=72
    (7*8)+(7*6)=98

    ReplyDelete
  12. a-3=45*9/9-9+102=a
    a*2=a
    a*a=3
    8*8=64a+a=3
    3*3=9+a=a
    this is the awnser 4 sure cause i know alot about math i know it all for this math problem for the harest and easyest cause this is a*a=3 then8*8=64cause if you add subtract divide multiply you get the problem and awnser ther is the awnser to the math problem this is realy easy because it is all in your bloode and brain i have the right awnser.......Thank you for reading this

    ReplyDelete
  13. = (b+o) * a where
    b = 2nd number
    o = order that the equation appears in or (a-1)
    a = first number
    answer = 98.

    ReplyDelete
  14. 1*a+2*b
    2*a+3*b
    3*a+4*b
    4*a+5*b
    and so on.......

    ReplyDelete
  15. 1*(2+3)+3=8
    2*(2+7)+7=27
    3*(2+5)+5=32
    4*(2+8)+8=60
    5*(2+7)+7=72
    6*(2+8)+8=98

    ReplyDelete
  16. a(a+b-1)
    2(2+3-1)=8
    3(3+7-1)=27
    4(4+5-1)=32
    5(5+8-1)=60
    6(6+7-1)=72
    7(7+8-1)=98

    ReplyDelete
  17. 2*1 + 3*2 = 8
    3*2 + 7*3 = 27
    4*3 + 5*4 = 32
    5*4 + 8*5 = 60
    6*5 + 7*6 = 72
    7*6 + 8*7 = 98

    ReplyDelete
  18. Answer is : 98
    Explanation:
    Here, 2+3=2*(3+1)= 8
    3+7=3*(7+2)= 27,
    4+5=4*(5+3)= 32,
    5+8=5*(8+4)= 60,
    6+7= 6*(7+5)= 72,
    Therefore,
    7+8= 7*(8+6)=98

    ReplyDelete
  19. 2*1+3*2=8
    3*2+7*3=27
    4*3+5*4=32
    5*4+8*5=60
    6*5+7*6=72
    7*6+8*7=98

    ReplyDelete
  20. selvakumar (a+b)-1*a

    ReplyDelete
  21. the answer is 98
    the formula is :
    (a+b)(a-1)+b
    simplified to :
    a(a+b-1)
    I enjoyed it!

    ReplyDelete
  22. nice question i got the answer 98

    ReplyDelete
  23. x * (x + y - 1), so 98

    ReplyDelete
  24. 98.
    This should have been rated as an easy puzzle.

    ReplyDelete
  25. 2+3=8,
    3+7=27,
    4+5=32,
    5+8=60,
    6+7=72,
    7+8=??

    (2+3)*2- 2=8
    (3+7)*3-3=27
    (5+8)*5-5=60
    (7+8)*7-7=98

    ReplyDelete
  26. 2+3=8,
    3+7=27,
    4+5=32,
    5+8=60,
    6+7=72,
    7+8=??

    (2+3)*2- 2=8
    (3+7)*3-3=27
    (5+8)*5-5=60
    (7+8)*7-7=98

    ReplyDelete
  27. 98

    the solution is,

    a*(a+b-1)
    example-
    if 7=a
    and 8=b
    then solution is
    7*(7+8-1) = 7*14 = 98

    ReplyDelete
  28. 98
    2*3+2
    3*7+6
    4*5+12
    5*8+20
    6*7+30
    7*8+42

    ReplyDelete
  29. This comment has been removed by the author.

    ReplyDelete
  30. 98 is right answer for without any formula we can think logically

    ReplyDelete
  31. ans is 106
    n(a)+m(b);n=1,2,3,4,5,6
    ;m=2,3,4,5,6,7

    ReplyDelete
  32. Answers : 98
    2+3=5-1=4*2=8
    3+7=10-1=9*3=27
    4+5=9-1=8*4=32
    5+8=13-1=12*5=60
    6+7=13-1=12*6=72
    7+8=15-1=14*7=98
    Sunil kumar

    ReplyDelete
  33. ans.98
    b+a*a-a
    8+7*7-7
    15*7-7
    105-7
    98

    ReplyDelete
  34. Ans : 98

    Logic:
    2*(3+1)=8
    3*(7+2)=27
    4*(5+3)=32
    5*(8+4)=60
    6*(7+5)=72
    7*(8+6)=98

    ReplyDelete
  35. The ans is 98

    ReplyDelete
  36. one more solution :
    2*3+(2)=8
    7*3+(2+4)=27
    4*5+(2+4+6)=32
    5*8+(2+4+6+8)=60
    6*7+(2+4+6+8+10)=72
    7*8+(2+4+6+8+10+12)=108

    Ans: 108

    ReplyDelete
  37. x+y = x*y + x(x-1)
    so
    7+8 => 56 + 42 => 98

    ReplyDelete
  38. (ab)+(a(a-1))=R

    Though I don't feel any accomplishement for finding an answer in less than 10 mins. Random pattern finding is what solves these type of problems.

    ReplyDelete
  39. 98, (a+b)*n+b , where n is the sequence no of equation.

    ReplyDelete
  40. 2 + 3 = 8 : 2* (2+3-1)
    3 + 7 = 27 : 3* (3+7-1)
    .
    .
    7+ 8 = 98 : 7*(7+8-1)

    ReplyDelete
  41. 2*(3+1)=8
    3*(7+2)=27
    .
    .
    .
    7+(8+6)=??? = 98

    ReplyDelete
  42. 98 that's quite simple

    ReplyDelete
  43. {(a*b)+i*a},where i=1,2,3....

    ReplyDelete
  44. 98
    bcoz
    2+3=2*[3+(2-1)=8
    3+7=3*[7+(3-1)=27
    4+5=4*[5+(4-1)=32
    5+8=5*[8+(5-1)=60
    6+7=6*[7+(6-1)=72
    Therefore
    7+8=7*[8+(7-1)]=98
    x+y=x[y+(x-1)=x^2+xy-x

    ReplyDelete
  45. since when 2+3=8? this is a wrong equality from the very beginning and against all math theories. 2+3=5 and therefore 7+8=15
    this is the answer.. :)

    ReplyDelete
  46. 2 * 3 + 2 =8
    3 * 7 + 6 =27,
    4 * 5 + 12 =32,
    5 * 8 + 20 =60,
    6 * 7 + 30 =72,
    7 * 8 + 42 = 98

    ReplyDelete
  47. you guys are smart..

    ReplyDelete
  48. There are lots of solutions to this. One set is of the form:
    f(x,y)=(1-n)x^2-2ny^2+(3n+1)xy-(12n+1)x+13ny+11n
    where n=0,1,2,3,...
    if n=0 then f(x,y)=x^2+xy-x which produces f(7,8)=98
    if n=1 then f(x,y)=-2y^2+4xy-13x+13y+11 so f(7,8)=120
    continue to get 142,164, 186,....

    ReplyDelete
  49. this is the way i solved it.....
    first i try to find the common pattern
    2,3=8 (8/2=4) and 2+3 =5 that means 4,5
    3,7=27 9,10
    4,5=32 8,9
    5,8=60 12,13
    6,7=72 12,13
    7,8 =98 14,15 in this case i first find 7+8 =15,,and 15-1=14,,,,then 14*7......98......

    ReplyDelete
  50. Poor notation ... any maths teacher writing 2+3=8 should be flayed alive. '+' has a well-defined meaning, it means 'add'. That is not what you are doing here, so you must not use '+'.

    You could either write it as 2*3=8 (although in type, you have to make it clear that that is not a multiplication sign), or more correctly f(2,3)=8.

    ReplyDelete
  51. Simplest formula:
    a(a+b-1)
    7*(7+8-1) = 98

    ReplyDelete